Mental health status of secondary school students: a meta-analysis of comparative studies between one-child and multi-child families in China - Zhang, Wei; Chen, Pan; Rao, Shu-Ying; Jiang, Yuan-Yuan; Su, Zhaohui; Cheung, Teris; Ng, Chee H.; Xiang, Yu-Tao; Wang, Gang (Frontiers in Psychiatry, 2025)
IntroductionMental health problems are common among secondary school students. However, when comparing one-child and multi-child families, the findings on the mental health of students are mixed. Therefore, we conducted a meta-analysis to compare the mental health status between secondary school students from one-child and multi-child families in China.MethodsRelevant studies using standard instruments on mental health (e.g., the Middle School Student Mental Health Scale; MSSMHS and the Mental Health Test; MHT) were searched in PubMed, Web of Science, PsycINFO, China National Knowledge Infrastructure (CNKI), and Wanfang. A random-effects model was employed to compute the pooled effect size. Subgroup analyses for categorical variables and meta-regression analyses for continuous variables were carried out to examine the potential moderators of group differences.ResultsWe identified 39 studies, which included 11,889 secondary school students from one-child families and 13,795 from multi-child families. No significant difference in mental health was found between students from one-child and multi-child families. However, significant group differences were observed in certain MHT domains, including Learning Anxiety [95% confidence interval (CI): -0.19; 0.00, I² = 0.0%, P = 0.04], Social Anxiety (95% CI:-0.25; 0.00, I² = 45.8%, P = 0.04), Tendency Towards Self-Blame (95% CI: -0.23; -0.07, I² = 0.0%, P < 0.01) and Allergic Tendencies (95% CI: -0.25; -0.01, I² =43.5%, P = 0.04).DiscussionThis meta-analysis did not show significant differences in the mental health between students from one-child and multi-child families. Future research should investigate the influence of socio-demographic factors, such as gender and place of residence, on the mental health of this population.Systematic review registrationhttps://inplasy.com/wp-content/uploads/2024/03/INPLASY-Protocol-5996.pdf, identifier INPLASY202430053.